2016
DOI: 10.1016/j.molmet.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying prorenin actions on hypothalamic neurons implicated in cardiometabolic control

Abstract: BackgroundHypertension and obesity are highly interrelated diseases, being critical components of the metabolic syndrome. Despite the growing prevalence of this syndrome in the world population, efficient therapies are still missing. Thus, identification of novel targets and therapies are warranted. An enhanced activity of the hypothalamic renin-angiotensin system (RAS), including the recently discovered prorenin (PR) and its receptor (PRR), has been implicated as a common mechanism underlying aberrant sympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 69 publications
2
19
1
1
Order By: Relevance
“…In a recent study, we showed that PRR is highly expressed in VP neurons and that their activation by PR evoked membrane depolarization and increased firing discharge. These effects were ANG II-independent and involved an increase in intracellular Ca 2ϩ levels and a Ca 2ϩ -dependent inhibition of a voltage-gated K ϩ current (34). Thus, our previous studies support that intracellular signaling cascades triggered by PR/PRR, rather than ANG II-AT 1 R indirect effects, mediate PR actions on VP neurons and VP release.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…In a recent study, we showed that PRR is highly expressed in VP neurons and that their activation by PR evoked membrane depolarization and increased firing discharge. These effects were ANG II-independent and involved an increase in intracellular Ca 2ϩ levels and a Ca 2ϩ -dependent inhibition of a voltage-gated K ϩ current (34). Thus, our previous studies support that intracellular signaling cascades triggered by PR/PRR, rather than ANG II-AT 1 R indirect effects, mediate PR actions on VP neurons and VP release.…”
supporting
confidence: 74%
“…In a recent study, we showed that PR stimulates the firing discharge of hypothalamic VP and presympathetic neurons through distinct ANG II-independent and -dependent mechanisms, respectively (34). PR effects on both cell types, however, involved binding of PR to PRR and the inhibition of a voltage-gated K ϩ channel in a Ca 2ϩ -dependent manner.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations